2017
DOI: 10.1016/j.geb.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Multicandidate elections: Aggregate uncertainty in the laboratory

Abstract: The rational-voter model is often criticized on the grounds that two of its central predictions (the paradox of voting and Duverger's Law) are at odds with reality. Recent theoretical advances suggest that these empirically unsound predictions might be an artifact of an (arguably unrealistic) assumption: the absence of aggregate uncertainty about the distribution of preferences in the electorate. In this paper, we propose direct empirical evidence of the effect of aggregate uncertainty in multicandidate electi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
0
10
1
2
Order By: Relevance
“…Bouton et al [6] and Bouton et al [7] are the first to hint at the fact that experimental elections with three alternatives may be different in that respect, but their underlying model is not quite the same as ours and so their findings do not really answer our question. The attention of the former paper is on comparing the efficiency of approval voting versus the simple plurality rule and the latter investigates Duverger's Law.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Bouton et al [6] and Bouton et al [7] are the first to hint at the fact that experimental elections with three alternatives may be different in that respect, but their underlying model is not quite the same as ours and so their findings do not really answer our question. The attention of the former paper is on comparing the efficiency of approval voting versus the simple plurality rule and the latter investigates Duverger's Law.…”
Section: Introductioncontrasting
confidence: 61%
“…Treatment 3 was chosen such that posterior probabilities for a type a voter were "in favor" of voting for alternative A. When considering voting for her type, type a faced the same pivotal probabilities as in treatment 2, so a voter voting for A found herself most likely pivotal in states b and c. 6 In this treatment, posterior probabilities and pivotal probabilities gave conflicting information and the differences in pivotal probabilities by far outweigh the differences in posterior probabilities. A naive voter using only posterior probabilities may vote for A exclusively in this treatment.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the third candidate never ranks first or second in samples 3 and 4, we cannot entirely exclude that some voters thought ex ante that she had a nonzero probability of winning. However, Bouton, Castanheira, and Llorente‐Saguer () showed that the sincere equilibrium also requires that voters give a sufficiently large probability to the existence of a state of nature where the third candidate has a stronger support than one of the top two, or that they give a positive probability to a full reversal of support between the third and the candidate ideologically closest. Both conditions seem unlikely to be satisfied when the third candidate lags far behind the top two in the first round.…”
Section: Interpretation Of the Results And Discussionmentioning
confidence: 99%
“…In this case, the right decision is simply the one that corresponds to the majority of signals. 8 In our context, a responsive pro…le is such that (i) at least some common value agents play action b with positive probability, and (ii) not all of them play b with probability 1. This ensures that, in equilibrium, some pivot probabilities are strictly positive -agents a¤ect the outcome of the vote with positive probability.…”
Section: Unbiased Signalsmentioning
confidence: 99%